PERENCANAAN BANK SAMPAH DALAM RANGKA PEMBERDAYAAN MASYARAKAT DI KECAMATAN KEPANJEN KABUPATEN MALANG - Wuri Sulistiyorini Purwanti; Sumartono .; Bambang Santoso Haryono (Universitas Tribhuwana Tunggadewi, 2015)
Waste management in Kepanjen Subdistrict particularly in community settlement area, still far from adequate. The community tend to dispose waste to river or burn it. In long term it leads to environmental pollution. Local government needs to plan and prepare budgeting to effectively manage waste. One of the method to overcome this problem is to plan waste bank by empowering the community so they could gain extra income. Thus, through this program it is expected to minimize waste accumulation and could give the community comprehension of how to manage their waste properly. The research focused on the process of waste bank planning formulation in Kepanjen Subdistrict of Malang Regency, and the supporting and constraining factors of waste bank planning formulation in Kepanjen Subdistrict of Malang Regency. Waste bank planning formulation process for community empowerment has been carry out through planning stages in the suitable provision, however the initiative comes from the beaurocracy, the community still needs contiguity in forming and managing the waste bank until they can fully manages their waste bank autonomically.